The Influence of Training and Creativity on Employee Performance With Teamwork as a Mediation Variable PT Penida Kreasi Persada - Lestari, Eka; Nurhayati , Mafizatun (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to analyze the influence of training and creativity on employee performance with teamwork as a mediating variable. The object of this research is the employees of PT. Penida Kreasi Persada. A total of 75 respondents filled out the questionnaire, samples were taken using the Slovin formula. This research was conducted from June 2022 to December 2022 at PT. Penida Kreasi Persada. The sampling technique used was proportional stratified random sampling. Data were analyzed using the SmartPLS (Partial Least Square) path analysis application. The results of this research indicate that training behavior has no effect on employee performance, and Creativity and Teamwork have a positive and significant effect on employee performance. Furthermore, the results show that Training and Creativity have a positive and significant effect on teamwork, and Training and Creativity have a positive and significant effect on employee performance which is mediated by teamwork at PT. Penida Kreasi Persada.